factories the following 4x+12x+9
Answers
Answered by
2
hey here is ur answer
4x^2 +6x+6x+9
=2x(2x+3)+3(2x+3)
=(2x+3)(2x+3)
=(2x+3)^2
or u can also factorise by identity
I hope this helps u
4x^2 +6x+6x+9
=2x(2x+3)+3(2x+3)
=(2x+3)(2x+3)
=(2x+3)^2
or u can also factorise by identity
I hope this helps u
Answered by
1
Your answer ⤵
___________________________✨
![4{x}^{2} + 12x + 9 = 0 \\ \\ 4{x}^{2} + 6x + 6x + 9 = 0 \\ \\ 2x ( 2x + 3 ) + 3 ( 2x + 3 ) \\ \\ 2x + 3 = 0 , 2x + 3 = 0 \\ \\ x = \frac{-3}{2} , x = \frac{-3}{2} 4{x}^{2} + 12x + 9 = 0 \\ \\ 4{x}^{2} + 6x + 6x + 9 = 0 \\ \\ 2x ( 2x + 3 ) + 3 ( 2x + 3 ) \\ \\ 2x + 3 = 0 , 2x + 3 = 0 \\ \\ x = \frac{-3}{2} , x = \frac{-3}{2}](https://tex.z-dn.net/?f=4%7Bx%7D%5E%7B2%7D+%2B+12x+%2B+9+%3D+0+%5C%5C+%5C%5C+4%7Bx%7D%5E%7B2%7D+%2B+6x+%2B+6x+%2B+9+%3D+0+%5C%5C+%5C%5C+2x+%28+2x+%2B+3+%29+%2B+3+%28+2x+%2B+3+%29+%5C%5C+%5C%5C+2x+%2B+3+%3D+0+%2C+2x+%2B+3+%3D+0+%5C%5C+%5C%5C+x+%3D+%5Cfrac%7B-3%7D%7B2%7D+%2C+x+%3D+%5Cfrac%7B-3%7D%7B2%7D)
___________________________✨
___________________________✨
___________________________✨
Similar questions